Development of an Innovative Media Design Assessment Model in Junior High School Chemistry Learning - Hairida (Postgraduate, University of Mataram, 2023)
An innovative assessment model comprises a set of procedures aimed at gathering information regarding both teacher-led learning and the learning outcomes delivered through technology, such as Quizizz and Google Forms. This research aims to develop an assessment model for junior high school chemistry courses and focus on designing innovative learning materials. This research uses the R&D method with a design thinking approach, this research employed three questionnaires. The questionnaire was dedicated to assessing the validity of the assessment model framework, the validity of the assessment design, and to conduct field trials involving both educators and students. The analysis outcomes demonstrated a notably high level of validity. The assessment model framework achieved an average CVI score of 0.99,